THE EVOLUTION OF THE ROLE OF CENTRAL BANKS IN POST-FINANCIAL CRISIS ECONOMIC STABILIZATION - Loso Judijanto; Oskar Hutagaluh (CV. Adiba Aisha Amira, 2024)
The 2008 global financial crisis has significantly changed the world's economic and financial landscape, forcing central banks to expand their role beyond the traditional mandate of inflation control. The research method in this study uses literature. The results show that central banks have broadened the scope of their interventions, adopting a more holistic approach to economic stability that includes not only price stability but also financial stability and economic growth. However, in this regard, there are challenges that central banks face in the digital age, including the emergence of digital currencies and financial technology.